Sociodemographic characteristics, knowledge and practice of personal hygiene with anemia incidence in adolescent girls - Dian Pertiwi; Apriningsih Apriningsih; Widayani Wahyuningtyas; Feda Anisah Makkiyah (Universitas Muhammadiyah Semarang, 2023)
Anemia is a serious global public health problem and affects the community especially in developing countries. The purpose of this study is to analyze the relationship between sociodemographic characteristics, knowledge and practice of personal hygiene with anemia incidence in adolescent girls in Sirnagalih Village, Jonggol, Bogor Regency. The research method used was observational analytic using quantitative data with cross sectional design. Respondents of this study were 78 adolescent girls with purposive sampling technique and according to the inclusion and exclusion criteria. The data was collected by test of hemoglobin levels and filling out a questionnaire with the google form. Based on the results of data analysis independent and dependent variables using the fisher exact test, age obtained p = 0,023, education obtained p = 0,058, knowledge of personal hygiene obtained p = 0,008, and practice of personal hygiene has p value = 0,045. The conclusion of this study, there is no relationship between education with anemia incidence. However, there is a relationship between variables of age, knowledge and practice of personal hygiene with anemia incidence in adolescent girls in Sirnagalih Village, Jonggol, Bogor Regency.